2017
DOI: 10.1136/bcr-2016-218338
|View full text |Cite
|
Sign up to set email alerts
|

Toothpick-induced aortoenteric fistula presenting as sepsis

Abstract: Aortoenteric fistulas (AEF) are a rare but life-threatening cause of gastrointestinal (GI) bleeding. We present the case of a primary AEF caused by ingestion of a toothpick by a 47-year-old male. This is the 10th known case in the literature in which a foreign body was found to be the cause of a communication between the aorta and the GI tract. Most foreign objects have been sewing needles; this is the first known case of a toothpick penetration. The patient presented to our institution with polymicrobial seps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The literature review has found highly varying symptoms from hematochezia to abscess formation, and fistula formation to aortoenteric fistula. In our case, the majority of patients (82%) reported just abdominal pain [ 3 ].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The literature review has found highly varying symptoms from hematochezia to abscess formation, and fistula formation to aortoenteric fistula. In our case, the majority of patients (82%) reported just abdominal pain [ 3 ].…”
Section: Discussionmentioning
confidence: 87%
“…The most common sites of impaction are reported to be the esophagus (2%), stomach (20%), duodenum (23%), small intestine (18%), and large intestine (37%) [ 8 ], but the literature review also reveals reports where the toothpick was found in the liver, pancreas, kidney, heart, bladder, ureter, and vasculature [ 4 , 9 , 10 ]. It can also lead to the formation of a fistula and pseudo-diverticulum as well as an abscess in different viscera [ 3 , 11 ]. These non-specific symptoms present a nightmare scenario for physicians and often lead to misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastrointestinal tract problems, such as malignancy, peptic ulcer disease, duodenal diverticulum, pancreatic pseudocyst, foreign body, or Billroth II gastric resection, may also contribute to secondary AEF. [3][4][5][6][7][8] Secondary AEF is more common than the primary type, although both are rare. The incidence of secondary AEF following aortic surgeries was reported to be 1.6% in a 36-year population-based study.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary AEF most commonly occurred in patients who had previous aortic surgery, with/without aortic prosthesis. Gastrointestinal tract problems, such as malignancy, peptic ulcer disease, duodenal diverticulum, pancreatic pseudocyst, foreign body, or Billroth II gastric resection, may also contribute to secondary AEF 3–8 . Secondary AEF is more common than the primary type, although both are rare.…”
Section: Introductionmentioning
confidence: 99%